The Impact of Requiring Completion of an Online Infection Control Course on Health Professionals’ Intentions to Comply with Infection Control Guidelines: A Comparative Study - Annalee Yassi; Elizabeth A Bryce; Deirdre Maultsaid; Helen Novak Lauscher; Kun Zhao (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Ensuring good infection control practice in health care facilities is a constant concern, yet evidence shows that the compliance of health care professionals with proper procedures is lacking, despite the existence of guidelines and training programs. An online infection control module was developed to provide ready access to training. Controversy exists about whether successfully completing such a course should be mandatory or strongly encouraged for all health care professionals. The objective of the present study was to compare the perception of safety culture and intention to comply with infection control guidelines in professionals who were required by their supervisors to take the course, and those who did so voluntarily.